Postural control deficits in participants with functional ankle instability as measured by the balance error scoring system - Docherty, C. L.; Valovich McLeod, T.; Shultz, S. J. (Clinical Journal of Sport Medicine, 2006)
Objective: To determine if postural control deficits are present in participants with functional ankle instability (FAI) as measured by the Balance Error Scoring System (BESS).